Comparison of Reading Speed after Bilateral Bifocal and Trifocal Intraocular Lens Implantation - Kim, Moses; Kim, Jae-hyung; Lim, Tae-Hyung; Cho, Beom Jin (Korean journal of ophthalmology, 2018)
To evaluate and compare visual acuity and reading speed for Korean language between a diffractive bifocal and trifocal intraocular lens (IOL) of the same material and haptic design. We reviewed the medical records of the patients who had undergone bilateral cataract surgery with bifocal IOLs (AT LISA 801) on the both eyes (bifocal group) and trifocal IOLs (AT LISA tri 839 MP, trifocal group). The main outcome measures were the uncorrected distance, intermediate, and near visual acuity (uncorrected distance visual acuity [UCDVA], uncorrected intermediate visual acuity [UCIVA], and uncorrected near visual acuity [UCNVA]) and corrected distance, near, and distance-corrected intermediate visual acuity (corrected distance visual acuity [CDVA], corrected near visual acuity [CNVA], and distance-corrected intermediate visual acuity [DCIVA]) at last postoperative follow-up month. Reading speeds for Korean language were measured to check near visual function. Fourteen eyes (7 patients) were included in the bifocal group and 32 eyes of 16 patients in the trifocal group. There were no statistical differences between the two groups with respect to UCDVA, UCNVA, CDVA, and CNVA. However, UCIVA (0.35 vs. 0.22 logarithm of the minimum angle of resolution [logMAR], p < 0.01) and DCIVA (0.34 vs. 0.20 logMAR, p < 0.01) were significantly better in the trifocal group than in the bifocal group. The mean reading speed for logMAR 0.5 optotype (point 10) was 86.50 words per minute (wpm) in the bifocal group and 81.48 wpm in the trifocal group without a significant difference (p = 0.70). Trifocal IOLs provided the same level of distance and near visual acuity and reading speed as that of bifocal IOLs with better intermediate visual acuity.